Answer :
Answer:
Step-by-step explanation:
expressed as
3x + 7y = 8- - - - - - - - - - - - -1
2x + 4y = 6- - - - - - - - - - - -2
Applying the method of elimination, we would eliminate x by multiplying equation 1 by 2 and equation 2 by 3. It becomes
6x + 14y = 16- - - - - - - - - - -3
6x + 12y = 18- - - - - - - - - - - -4
Subtracting equation 4 from equation 3, it becomes
2y = - 2
Dividing the left hand side and the right hand side of the equation by 2, it becomes
2y/2 = - 2/2
y = - 1
Substituting y = - 1 into equation 1, it becomes
3x + 7 × - 1 = 8
3x - 7 = 8
Adding 7 to the left hand side and the right hand side of the equation, it becomes
3x - 7 + 7 = 8 + 7
3x = 15
Dividing the left hand side and the right hand side of the equation by 3, it becomes
3x/3 = 15/3
x = 5